Legal Protection for Victims of Acute Kidney Injury in Children Caused by Hazardous Syrup Medicines in Indonesia - Yudiyanto, Ade Rachmat; Sulistyawaty, Sri; Pakpahan, Kartina (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the legal protection for victims of acute kidney failure in children caused by the consumption of syrup-based medicines containing diethylene glycol (DEG) and/or ethylene glycol (EG) in Indonesia. Using a normative juridical method, this article analyzes relevant legislation concerning victim assistance, the rights of victims' families under the Consumer Protection Law, and the implementation of legal accountability by the government, the National Agency of Drug and Food Control (BPOM), and pharmaceutical businesses. The findings reveal that although a legal framework is in place, significant challenges persist in law enforcement and the fulfillment of victims' rights. Therefore, it is necessary to strengthen consumer protection mechanisms and enforce strict legal measures to prevent similar cases from recurring and to ensure justice for the victims